Development of a droplet digital PCR method for the detection of Ureaplasma urealyticum - Yong-Zhuo Zhou; Yun-Hu Zhao; Yan-Lan Chen; Hua Luo; Yu-lin Zhou; Bing Gu; Wei-Zhen Fang; Chao-Hui Duan; Xu-Guang Guo (Practical Laboratory Medicine)
Background: Human infection with Ureaplasma urealyticum(UU) is mainly manifested as non-gonococcal urethritis, where it can lead to cervicitis, premature rupture of membranes and abortion in women, as well as infertility in males, which becomes a major problem in clinical diagnosis and treatment. At present, real-time fluorescence quantitative PCR and culture are the two main methods for detecting UU. The real-time fluorescence quantitative PCR method is cumbersome and cannot accomplish absolute quantification on nucleic acids, while the cultivation method has limitations such as low sensitivity and being time-consuming. The aim of this study is to establish a more rapid and accurate droplet digital PCR(ddPCR) method for the detection of UU. Methods: Primers were designed for the ParC gene of UU. Nucleic acids from a standard strain of UU were extracted. Specificity, sensitivity, and repeatability detection was performed using ddPCR, and the detection performance of ddPCR was evaluated. Results: The detection process could be completed in 92 min. It has a high sensitivity of up to 3.8 pg/μL. With a high specificity, no positive microdrop were detected in eight negative control pathogens in this experiment. In addition, ddPCR detection of UU has good repeatability, and the calculated CV is 2.1 %. Conclusion: Our data indicated that ddPCR detection technology has the characteristics of absolute quantification, high stability, high specificity and high sensitivity of UU. It can promote the accurate detection of UU, providing a more scientific basis for clinical diagnosis and treatment.